Penerapan Metode Quranuna Untuk Meningkatkan Kemampuan Siswa Menghapal Al-Qur'an Pada Program Tahfidz Dan Baca Tulis Al-Qur'an - Nurhasan Nurhasan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research focused on the tahfidz Al Qur`an program including institution profiles, background, vision and mission, and planning the pattern of learning tahfidz and reading and writing the Qur`an using the Quranuna method. The process of implementing the Quranuna method includes the learning process in the classroom starting from the opening, the process of memorizing classically with the standard rhythm of the Quranuna method, and evaluation in the form of rote tests and group learning processes. This study uses a qualitative approach with descriptive methods with data collection techniques including observation, interviews, tests, documentation, and literature study. While data analysis uses data reduction (data reduction), data presentation (data display) and verification (conclusion drawing). The results showed that the results obtained in the application of the Quranuna method by using a test were that in general students got a score of "Very Good" with a score of 9.00-10.00. But there are 2 students out of 72 students who get a "Good" score with a score of 7.6-8.9. The results obtained in tahfidz learning used the TITANIQ method (Tilawah, Tahfidz, Writing and Understanding the Qur'an) the method used before the Quranuna method at MI At Taqwa as of June 29 2004, that is, students generally get a score of "Enough" with the score is from 6.0-7.5 totaling 43 people. While other students who got a "Good" score with a score of 7.6-8.9 totaled 28 people and students who got a "Very Good" grade with a score of 9.00-10.00 totaled 1 person. Thus it is very clear that the Quranuna method can improve students' memorization of the Qur'an.